Synthesis of Bi2Se3 quantum dots as a highly selective luminescence probe of 1-chloro-2,4-dinitrobenzene - Tang, Xiao-Min; Chu, Wen-Xin; Chen, Qiao-Yu; An, Bao-Li; Zhang, Ji-Ming; Wang, Xiao-Hong; Xu, Jiaqiang (Journal of photochemistry and photobiology. A, Chemistry., 2025)
Bi2Se3 quantum dots as a highly selective luminescence probe of 1-chloro-2,4-dinitrobenzene. [Display omitted] •Yellow-green luminescent Bi2Se3 QDs has been firstly synthesized with quantum yield of 13.8%.•The synthesized Bi2Se3 QDs had high selectivity for 1-chloro-2,4-dinitrobenzene (CDNB).•The detection limit of CDNB as low as 0.03 μM (6.08 ng/ml).•This work can provide new sight for finding highly selective luminescent probe of organic compounds. 1-Chloro-2,4-dinitrobenzene (CDNB) is a highly allergenic compound, it is widely used for the quantitative detection of glutathione-s-transferase. This chemical in environment can cause serious effects on human health. High-performance liquid chromatography (HPLC) with ultra violet detector has been used to detect CNDB, and the limit of the detection (LOD) is 200 ng/ml. It is significant to find a simple and quick method to detect CDNB. It is still a challenge to detect CDNB from nitroaromatic compounds with alike structure of CDNB using luminescent probe method. In this work, yellow-green Bi2Se3 quantum dots (QDs) were firstly synthesized by solvothermal method, and its absolute luminescence quantum yield reached 13.8 ± 0.2 %. Bi2Se3 QDs are environmentally friendly luminescent materials. The luminescence of the Bi2Se3 QDs solution was selectively quenched by CDNB molecules, CDNB could be selectively detected using Bi2Se3 QDs as luminescent probe. The linear range was 0.040 ∼ 0.50 μM, and the detection limit was 0.03 μM. Some nitroaromatic compounds including 4-fluoro-1,2-dinitrobenzene (4-F-1,2-DNB), 1,3-dinitrobenzene (1,3-DNB), 2,6-dinitroaniline (2,6-DNA), p-chloronitrobenzene (p-CNB), 1-methyl-4-nitrobenzene (1-M−4−NB), 1-iodo-4-nitrobenzene (1-I-4-NB) and 1-(4-nitro-phenyl)-ethanone (4-NPE) did not interfere with the detection of CDNB. The detection of CDNB was interfered slightly only by 2,4-dinitroaniline (2,4-DNA) due to inner filter effect. The reason for the highly selective detection of CDNB using Bi2Se3 QDs was investigated detailed. The result provides a new sight for finding highly selective luminescent probe for organic chemicals based on the intermediate state formed between the surfaces of luminescent Bi2Se3 QDs and organic molecules through the characteristic second bond. Bi2Se3 QDs provide a new candidate for highly selective luminescent probe of CDNB with low limit of detection of 6.08 ng/ml.